Gastric Linitis Plastica and role of endoscopic ultrasound: an under-recognised diagnostic modality. - Aujla, Usman Iqbal; Jabbar, Sadia; Atique, Muhammad (Journal of the Pakistan Medical Association, 2022)
Gastric linitis plastica is an aggressive malignancy with poor prognosis. Timely diagnosis is important for effective management. However, the conventional endoscopic biopsies are often inconclusive leading to delay in diagnosis and subsequent management. We present a case of a 55-year old female with high suspicion of gastric linitis plastica on gastroscopy with repeated negative endoscopic biopsies. She underwent an endoscopic ultrasound fine needle aspiration (EUS-FNA) at our center with establishment of diagnosis of gastric malignancy. There are no established guidelines about the role of EUS-FNA as a sequential diagnostic modality for this tumour. However, EUS-FNA is a highly sensitive modality to establish diagnosis in challenging cases where routine endoscopy remains inconclusive. Keywords: Gastric linitis plastica, Endoscopic ultrasound, Fine needle aspiration. Continuous...